2012
DOI: 10.3354/meps10034
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to multiple foraging habitats enhances seabirds’ resilience to local food shortages

Abstract: As central-place foragers, seabirds from colonies located close to multiple and/or productive marine habitats might experience increased foraging opportunities and enhanced resilience to food shortages. We tested whether this hypothesis might explain divergent trends in 3 populations of black-legged kittiwakes Rissa tridactyla, a surface-feeding piscivore, in the eastern Bering Sea. We simultaneously studied the foraging behavior, diet, nutritional stress, and breeding performance of chick-rearing kittiwakes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 72 publications
2
63
1
Order By: Relevance
“…The other colonies did not statistically gain or lose, but trended towards slight increases in telomere length, although variability is large. Bogoslof, a colony with evidence for high food availability and increasing seabird populations [43,44], showed the most evidence for telomere length increases, and also the longest telomere lengths. St. Paul and St. George are colonies where populations are relatively stable yet nutritional stress is often high [33]; on these colonies birds maintained, but did not significantly gain or lose, TL.…”
Section: Discussionmentioning
confidence: 99%
“…The other colonies did not statistically gain or lose, but trended towards slight increases in telomere length, although variability is large. Bogoslof, a colony with evidence for high food availability and increasing seabird populations [43,44], showed the most evidence for telomere length increases, and also the longest telomere lengths. St. Paul and St. George are colonies where populations are relatively stable yet nutritional stress is often high [33]; on these colonies birds maintained, but did not significantly gain or lose, TL.…”
Section: Discussionmentioning
confidence: 99%
“…During summer, many seabirds are central-place foragers, tied to a breeding colony while incubating eggs or feeding chicks. Central-place foraging constraints during the summer breeding period restrict foraging to varying radii around colonies to meet the energy demands of nestling growth and self-maintenance (Burke & Montevecchi 2009, Paredes et al 2012, Harding et al 2013. During fall, seabirds are not constrained to forage from a central place or a nest-bound chick and, therefore, might change diets and spatial habitat affinities compared to those in summer.…”
Section: Introductionmentioning
confidence: 99%
“…The Bering Sea Project, along with prior ecosystem and long-term ecological studies, demonstrated that juvenile (age-0 to 1) walleye pollock Gadus chalcogrammus and euphaussiids (krill) were key prey items for seabirds in the SEBS in recent decades; however, capelin Mallotus villosus, sand lance Ammodytes hexapterus, and other prey also were regionally or historically important (Springer et al 1986, Sinclair et al 2008, Renner et al 2012, Harding et al 2013). Many seabird species in the Bering Sea are omnivorous, consuming different species of zooplankton and fishes, spatially between colonies or ecoregions, seasonally, and when self-feeding vs. provisioning chicks (Hunt et al 2002a, Paredes et al 2012, Renner et al 2012, Harding et al 2013. Abundance of these prey species can vary greatly by season, year, and region (Brodeur et al 1999, Hollowed et al 2012, Parker-Stetter et al 2013, Ressler et al 2014; for example, physical forcing from wind and winter sea ice extent over the shelf can greatly affect the distribution and abundance of fish populations in the SEBS (Hunt et al 2002b, Stabeno et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial and temporal heterogeneity in bird breeding habitat can cause variation in individual productivity and survival, and thus variation in demographic parameters (Donovan et al 1995, Paredes et al 2012, Aubry et al 2013, Catry et al 2013) and population size (Holmes & Sherry 2001, Amar et al 2011. Anthropogenic changes in habitat extent and quality have been the most important cause of declines in terrestrial biodiversity, particularly birds, in the past century (Sala et al 2000, Green et al 2005.…”
mentioning
confidence: 99%